HUBUNGAN ANTARA STATUS SOSIAL EKONOMI ORANG TUA DENGAN PRESTASI PESERTA DIDIK - Abidzar Al Ghifari; Nur Khasanah (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the relationship between parents’ socioeconomic status and students’ academic achievement through a library research approach. Parents’ socioeconomic status in this study includes educational level, occupation, and income, which indirectly influence learning opportunities, access to educational resources, and the quality of educational support received by students. The research method was conducted by reviewing and synthesizing various relevant literature sources, including academic books, national and international journal articles, and previous research findings related to the topic. The results of the literature analysis indicate that students from families with higher socioeconomic status tend to achieve better academic performance due to the availability of adequate learning facilities, a supportive academic environment, and positive emotional and academic support from parents. However, the findings also reveal that socioeconomic status is not the sole determinant of academic achievement. Non-economic factors such as students’ intrinsic learning motivation, teacher support, school quality, and a positive social environment play a significant role in enabling students from lower socioeconomic backgrounds to attain high academic performance. Therefore, it can be concluded that parents’ socioeconomic status has an influence on students’ academic achievement, but this influence is not deterministic. This study recommends that educational policies should focus on equalizing learning opportunities through scholarship programs, improving teacher competence, and strengthening collaboration among schools, families, and communities to support students’ academic success.